2009
DOI: 10.1016/j.enggeo.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mechanisms for landslide type initiation of debris flows

Abstract: The modelling of debris flow initiation in slopes is addressed in this paper. First, possible factors governing debris flow initiation are established. Then, a coupled hydro-mechanical model for deformable porous media with two pore fluids that is used to assess the problem of the debris flow initiation in slopes is briefly outlined. Various ways to identify failure and to approach the transition of the failed mass into a debris flow are discussed in the framework of small strain theory and elasto-plastic beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 30 publications
(30 reference statements)
1
22
0
Order By: Relevance
“…Klubertanz et al 2009;Jakob and Hungr 2005;Iverson 1997). However, it is clear that occurrence of a debris flow requires large volumes of sediment to be available, either on slopes or in a stream channel, and steep slopes to allow rainfall and/or streamflow of sufficient intensity to mobilise the sediment.…”
Section: Debris Flowsmentioning
confidence: 94%
“…Klubertanz et al 2009;Jakob and Hungr 2005;Iverson 1997). However, it is clear that occurrence of a debris flow requires large volumes of sediment to be available, either on slopes or in a stream channel, and steep slopes to allow rainfall and/or streamflow of sufficient intensity to mobilise the sediment.…”
Section: Debris Flowsmentioning
confidence: 94%
“…It is shown that the model (21) is applicable to both initially and fully developed plastic deformation of granular materials with drained or undrained conditions [41,43]. It will reduce to the original one (16) when the void ratio e is equal to the critical value e crt from (22) and (23). It means, for same material, same constants c 1 $ c 4 will be obtained for the original and extended models in the case of e ¼ e ecrt .…”
Section: Introductionmentioning
confidence: 78%
“…Numerical analysis plays an important role to obtain this information, where a competent constitutive model for debris materials is required. The main factors influencing the initiation of debris flow are, among others, the topography, material parameters, water and the initial stress state in the affected slope [22]. Earth slopes with inclinations ranging from 26 to 45 have been generally identified as most prone to debris flow initiation [40].…”
Section: Introductionmentioning
confidence: 99%
“…The hydromechanical behaviour of the involved volcanic ash has been characterised by means of a comprehensive experimental laboratory testing program [17,18], thus enabling the use of a physically-based model for seepage and slope stability analyses. Compared to more detailed geomechanical models at the local slope scale [19][20][21], the model described hereafter allows a pragmatic, general exploration of the effects of a series of wet season rainfall events on slope stability as a function of soil hydraulic and strength properties, as well as slope inclination.…”
Section: Physically-based Approach For the Preliminary Establishment mentioning
confidence: 99%